Digital-Based Sharia Marketing Strategy to Increase Sales at The Ciwaringin Natural Dye Writing Batik Center Cirebon : Case Study at "Kebon Gedang Batik Center" Ciwaringin Cirebon - Inayah Inayah; Ananda Tri Cahyati; Ari Saputra; Muhammad Viky; Dini Selasih (Jurnal Indonesia Sosial Sains, 2024)
The presence of MSMEs plays a crucial role in driving the Indonesian economy forward. "Batik Tulis Kebon Gedang Center" as one of the traditional batik MSMEs in Ciwaringin has recently risen after experiencing the impacts of COVID-19. This study aims to identify and analyze effective economic strategies to address the challenges of the digital era for the community in the "Batik Tulis Kebon Gedang Center" in Ciwaringin, Cirebon. The research method used is a qualitative approach through in-depth interviews and observation with the batik community. The results of this research, it can be observed that the "Batik Tulis Kebon Gedang Center" community adopts various economic strategies in facing various challenges in the digital era, including competition with digital batik products, changes in consumer behaviour, and limitations in the online market penetration. Based on these findings, several economic strategies are formulated, including increasing online presence through e-commerce platforms which have become a trend among the community and shorby (business link), using several promotional mixes such as advertising, sales promotion, public relations, and publications, direct marketing, collaboration with digital designers and influencers, as well as increasing digital literacy among batik community members. The implementation of these strategies is expected to strengthen the competitiveness and sustainability of the "Batik Tulis Kebon Gedang Center" in the digital era.